MiR-421 Binds to PINK1 and Enhances Neural Stem Cell Self-Renewal via HDAC3-Dependent FOXO3 Activation - Jiang, Yugang; Jia, Jiaoying; Liu, Min; Tan, Zhigang; Cui, Yan (Frontiers in Cell and Developmental Biology, 2021)
Dysfunctions of neural stem cells (NSCs) often lead to a variety of neurological diseases. Thus, therapies based on NSC have gained increasing attentions recently. It has been documented that microRNA (miR)-421 represses the autophagy and apoptosis of mouse hippocampal neurons and confer a role in the repair of ischemic brain injury (IBI). Herein, we aimed to illustrate the effects of miR-421 on NSC self-renewal. The downstream factors of miR-421 were predicted initially, followed by gain- and loss- of function assays to examine their effects on NSC self-renewal. Immunoprecipitation and dual luciferase assays were conducted to validate the interaction among miR-421, PTEN-induced putative kinase 1 (PINK1), HDAC3, and forkhead box O3 (FOXO3). A mouse model with IBI was developed to substantiate the impact of the miR-421/PINK1/HDAC3/FOXO3 axis on NSC self-renewal. The expression of miR-421 was down-regulated during differentiation of human embryonic NSCs, and miR-421 overexpression accelerated NSC self-renewal. Besides, miR-421 targeted PINK1 and restricted its expression in NSCs, and further suppressed HDAC3 phosphorylation and enhanced FOXO3 acetylation. In conclusion, our data elucidated that miR-421 overexpression may facilitate NSC self-renewal through the PINK1/HDAC3/FOXO3 axis, which may provide potential therapeutic targets for the development of novel therapies for IBI.